Pre-operative and early postoperative health-related quality of life of breast cancer woman: a Lebanese prospective study - Rana El Haidari; Virginie Nerich; Linda Abou-Abbas; Fadi Abdel-Sater; Amelie Anota (BMC, 2023)
Abstract Breast cancer (BC) is a major health concern in Lebanon, with an increasing incidence rate due to advancements in treatment modalities. Evaluating the impact of the BC and its treatment on a woman's Health-Related Quality of Life (HRQoL), and comparing these patterns before and after breast conserving surgery is important to identify areas where interventions may be needed to improve the overall well-being of women with BC. This study aimed to evaluate the HRQoL pre and post-operative breast conserving surgery and just prior to initiation of adjuvant therapy in newly diagnosed patients with BC in Lebanon, specifically focusing on changes in body image. A prospective cohort study was conducted on 120 patients in two health care facilities in Lebanon, collecting sociodemographic and clinical data, and using the EORTC QLQ-C30 and QLQ-BR23 questionnaires to evaluate HRQoL. The outcomes were measured at baseline and then one-day post-operative breast surgery. Results revealed a statistically and clinically significant decrease in body image (mean difference of 8.1 points (95% 4.3;11.1)), physical functioning (mean difference of 6.1 points (95% 3.3;8.5)), and emotional functioning (mean difference of -8.4 points (95%-12.4; -4.9) after surgery. Positive change of physical functioning score was observed among married women. Positive change of emotional functioning score was observed among patients with poor body image score and high future perspective score. Our findings provide valuable insights for clinicians and researchers on the impact of breast conserving surgery on HRQoL in Lebanese women.